2016
DOI: 10.1002/hed.24672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of cancer cachexia based on time from treatment in advanced-stage head and neck squamous cell carcinoma

Abstract: Cachexia prevalence at 6 and 12 months after treatment for HNSCC indicates a higher chance of recurrence, NCHE, and death. © 2016 Wiley Periodicals, Inc. Head Neck 39: 716-723, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 22 publications
2
31
1
5
Order By: Relevance
“…The present study also showed that pretreatment muscle wasting is an independent prognostic factor for OS in LAHNSCC patients. Kaplan–Meier and Cox regression analyses showed a significantly worse OS in patients with pretreatment muscle wasting, which is consistent with previous studies …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study also showed that pretreatment muscle wasting is an independent prognostic factor for OS in LAHNSCC patients. Kaplan–Meier and Cox regression analyses showed a significantly worse OS in patients with pretreatment muscle wasting, which is consistent with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…In this Dutch patient cohort, an FFMI < P 10 was found in 29% ( n = 40/137) of the patients at the start of CRT, which is slightly higher than reported in present literature . Kwon et al reported a much lower pretreatment incidence of cachexia in Korean patients, namely, 6.1% ( n = 22/361) . These differences can probably partially be explained by the different diagnostic criteria that were used for muscle wasting and cachexia .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Up to over 50% of advanced head and neck cancer (HNC) patients present to their initial clinic visit in this catabolic state . Many present with a several month history of dysphagia or odynophagia related to the location of their tumor or an enlarging neck mass.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] Up to over 50% of advanced head and neck cancer (HNC) patients present to their initial clinic visit in this catabolic state. [11][12][13][14] Many present with a several month history of dysphagia or odynophagia related to the location of their tumor or an enlarging neck mass. Other social factors common to this population, such as alcohol abuse, further complicate their nutritional status.…”
Section: Introductionmentioning
confidence: 99%